Role of hyperuricemia in diabetic nephropathy - DENG Jie, WEI Jiali (Jichu yixue yu linchuang)
Hyperuricemia (HUA), characterized by abnormal uric acid (UA) metabolism, leads to the accumulation of urate salts within the kidney. This accumulation not only disrupts glomerular filtration and tubular reabsorption functions but also triggers oxidative stress, inflammation,and up-regulating the renin-angiotensin-aldosterone system (RASS), all of which damage renal cells and tissues. These mechanisms contribute to renal fibrosis and accelerate the progression of diabetic nephropathy (DN)/diabetic kidney disease(DKD). These findings underscore the role of HUA as a risk factor for the advancement of DKD, emphasizing the critical importance of effective UA control in delaying its development.